Pande et al_2018_microsatellite - Pande, Anant; Rawat, Nidhi; Sivakumar, Kuppusamy; Sathyakumar, Sambandam; Mathur, Vinod B; Mondol, Samrat (Dryad Digital Repository, 2018)
Genotype data generated from cross-species microsatellite markers for Snow Petrel and Wilson's Storm Petrel.